Recent Inflationary Trends in World Commodities Markets - Krichene, Noureddine (IMF Working Papers; Working Paper, 2008)
Expansionary monetary policies in key industrial countries and sharply depreciating U.S. dollar exchange rate sent commodities prices soaring at unprecedented rates during 2003-2007. Food prices rose to alarming levels threatening malnutrition and food riots. In contrast, consumer price indices, a leading indicator for monetary policy, were showing almost no inflation and posed a price puzzle insofar their evolution was not responsive to record low interest rates, double digit commodities inflation, and sharp exchange rate depreciation. Commodities prices were shown to be driven by one common trend, identified as a monetary shock. Policy makers may have to face a policy dilemma: maintain monetary policy stance with accelerating commodities price inflation, subsequent world recession, and financial disorder; or tighten monetary policy with subsequent world recession followed by recovery and financial and price stability.